(untitled) (Simbiótica. Revista Eletrônica, 2024)
The New High School (NEM) and the National Common Curricular Base (BNCC) have directly impacted the construction of textbooks acquired through the National Textbook and Teaching Material Program (PNLD). In the 2021 edition of PNLD, the disciplinary book for each of the four Humanities and Social Sciences subjects was replaced by a single work, organized by area of knowledge. In light of the questions raised in the article "The three generations of sociology textbooks in Brazil (1920-2016)", we seek to understand whether the textbook resulting from PNLD 2021 can still be categorized as the third generation of Sociology textbooks or if it establishes a rupture significant enough to inaugurate a new generation.